2016
DOI: 10.1007/s11356-016-6690-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo exposure of the marine clam Ruditapes philippinarum to zinc oxide nanoparticles: responses in gills, digestive gland and haemolymph

Abstract: Potential nanoparticle (NP) toxicity poses a growing concern in marine coastal environments. Among NPs, zinc oxide nanoparticles (nZnO) are widely used in many common products that ultimately become deposited in coastal habitats from multiple non-point sources. In this study, we evaluated the in vivo effects of nZnO in the clam Ruditapes philippinarum. Animals were exposed to nZnO (1 and 10 μg/L) and ZnCl2 (10 μg/L) for 7 days. ZnCl2 was used to compare the effects of the NPs to those of Zn(2+) and to ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 94 publications
3
24
0
Order By: Relevance
“…Their exceptional broad-spectrum bactericidal properties and biocompatibility (i.e. as drug delivery agent) have also made AgNP extremely useful in a diverse range of consumer goods (Luoma 2008;Rainville et al 2014;Cozzari et al 2015;Katsumiti et al 2015;Marisa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their exceptional broad-spectrum bactericidal properties and biocompatibility (i.e. as drug delivery agent) have also made AgNP extremely useful in a diverse range of consumer goods (Luoma 2008;Rainville et al 2014;Cozzari et al 2015;Katsumiti et al 2015;Marisa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide AgNP production is estimated at % 55 tonne/yr (Piccinno et al 2012). However, release of AgNP into aquatic environs can happen through wastewaters generated during AgNP synthesis and/or incorporation into goods and consumer products (Canesi et al 2012;Matranga & Corsi 2012;Katsumiti et al 2015;Marisa et al 2016). As such, AgNP have emerged as potential stressors that might enter marine environment (Luoma 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, ROS may promote the oxidation of proteins, a process known as protein carbonylation (PC) which constitutes the most common type of PTM triggered by oxidative stress (Cattaruzza and Hecker, 2008;Suzuki et al, 2010 In general, the present results showed no alteration on PC levels in ). mussels, with similar PC levels in non-contaminated and contaminated mussels exposed to submersion and tide conditions Similarly, Marisa et al (2016) showed no significant differences .…”
Section: Oxidative Damagementioning
confidence: 76%
“…Moreover, an increase in the immune cell number was found in other marine invertebrates in response to different stimuli. For example, hemocytes increased in the mollusc Ruditapes philippinarum after treatment with zinc oxide nanoparticles (Marisa et al., ).…”
Section: Discussionmentioning
confidence: 99%